2010
DOI: 10.1002/stem.453
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Multiple Niches for Hematopoietic Stem Cell Regulations

Abstract: Two types of stem cell niches in bone marrow (BM), endosteal osteoblastic, and vascular niches are involved in the microenvironmental regulation of hematopoietic stem cells (HSCs). Recently, redundant features of the two niches were identified, based on their common cellular origins or chemical mediators being produced in each niche. In contrast, studies have also revealed that HSCs are localized differentially in the niches with respect to their distinct functional status, and that the biological activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…We first compared the expression levels of Jagged and CXCL-12, the two cross-talk molecules known to play major roles in supporting HSCs both under in-vivo and in-vitro conditions [6, 13]. As shown in Fig 2A and 2B, each independent line of MSCs cultured under stimulatory conditions exhibited higher level expression of CXCL-12 and Jagged-1 than those with non-stimulatory serum, suggesting that these MSCs can show potential differences in their niche cross-talk with HSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first compared the expression levels of Jagged and CXCL-12, the two cross-talk molecules known to play major roles in supporting HSCs both under in-vivo and in-vitro conditions [6, 13]. As shown in Fig 2A and 2B, each independent line of MSCs cultured under stimulatory conditions exhibited higher level expression of CXCL-12 and Jagged-1 than those with non-stimulatory serum, suggesting that these MSCs can show potential differences in their niche cross-talk with HSCs.…”
Section: Resultsmentioning
confidence: 99%
“…In BM, the MSCs comprise both perivascular and endosteal niche [6]; a subset of mesenchymal stromal cells (MSCs) that retain colony-forming potential (CFU-F) and self-renewal ability could reconstitute both types of niches in the heterologous marrow model [7, 8]. Subsequent studies also showed that BM MSCs expressing nestin [9], leptin-receptor [10], or prx-1 [11] are enriched with CFU-F and play a major role as a niche in BM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both forms of bone marrow contain extensive numbers of blood vessels and capillaries [81]. Microscopically, osteoblastic niches are spatially separated from vascular niches that provide a systemically enriched oxygen source within the bone marrow [82-85] (Fig. 1).…”
Section: Megakaryocyte and Platelet Biologymentioning
confidence: 99%
“…The bone-forming osteolineage cells results in high local concentrations of Ca 2+ , and the Ca 2+ -sensing receptor promotes the engraftment of HSCs (Adams et al, 2006). In the perivascular niche, endothelial and mesenchymal stem cells, together with sympathetic nerve fibers, modulate HSC behavior (Oh and Kwon, 2010). A major regulator of stem cell function is the Notch receptor system, which ensures a proper balance between stem cells and their progeny by preventing or favoring cell commitment.…”
Section: The Niche: Stem Cells and Supporting Cellsmentioning
confidence: 99%